Pengaruh Kualitas dan Harga Terhadap Minat Beli Konsumen pada UMKM Kripik Piksun Desa Nagrak Kecamatan Pacet, Kabupaten Bandung - Siti Rahmawati; Halimah Zahrah (Indo Publishing, 2026)
This study aims to determine the influence of price and word of mouth (WOM) on consumer purchase intention at the Keripik Piksun MSME in Nagrak Village, Pacet District, Bandung Regency. The research method used was quantitative, with data collection through questionnaires and interviews. The sample size was 222 respondents, determined using the Slovin formula with a 5% margin of error. Data analysis was conducted using multiple linear regression analysis, validity tests, reliability tests, normality tests, multicollinearity tests, t-tests, and the coefficient of determination (R²). The results showed that price had a positive and significant effect on consumer purchase intention, and word of mouth also had a positive and significant effect on consumer purchase intention. Simultaneously, price and word of mouth had a significant effect on consumer purchase intention, with a coefficient of determination of 57.9%. The remaining influence was influenced by other variables outside the study. Word of mouth had a more dominant influence than price. This research is expected to provide considerations for MSMEs in setting appropriate prices and improving word of mouth strategies to increase consumer purchase intention